Maize plant expresses SWEET transporters differently when interacting with Trichoderma asperellum and Fusarium verticillioides, two fungi with different lifestyles - López-Coria, Montserrat; Guzmán-Chávez, Fernando; Carvente-García, Roberto; Muñoz-Chapul, Daniela; Sánchez-Sánchez, Tomás; Arciniega-Ruíz, Juan Manuel; King-Díaz, Beatriz; Sánchez-Nieto, Sobeida (Frontiers in Plant Science, 2023)
Most Trichoderma species are beneficial fungi that promote plant growth and resistance, while Fusarium genera cause several crop damages. During the plant-fungi interaction there is a competition for sugars in both lifestyles. Here we analyzed the plant growth promotion and biocontrol activity of T. asperellum against F. verticillioides and the effect of both fungi on the expression of the maize diffusional sugar transporters, the SWEETs. The biocontrol activity was done in two ways, the first was by observing the growth capacity of both fungus in a dual culture. The second one by analyzing the infection symptoms, the chlorophyl content and the transcript levels of defense genes determined by qPCR in plants with different developmental stages primed with T. asperellum conidia and challenged with F. verticillioides. In a dual culture, T. asperellum showed antagonist activity against F. verticillioides. In the primed plants a delay in the infection disease was observed, they sustained chlorophyll content even after the infection, and displayed upregulated defense-related genes. Additionally, the T. asperellum primed plants had longer stems than the nonprimed plants. SWEETs transcript levels were analyzed by qPCR in plants primed with either fungus. Both fungi affect the transcript levels of several maize sugar transporters differently. T. asperellum increases the expression of six SWEETs on leaves and two at the roots and causes a higher exudation of sucrose, glucose, and fructose at the roots. On the contrary, F. verticillioides reduces the expression of the SWEETs on the leaves, and more severely when a more aggressive strain is in the plant. Our results suggest that the plant is able to recognize the lifestyle of the fungi and respond accordingly by changing the expression of several genes, including the SWEETs, to establish a new sugar flux.